2017
DOI: 10.18805/lr-358
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity studies of alfalfa germplasm (Medicago sativa L. subsp. sativa) of United States origin using microsatellite analysis

Abstract: This study aimed to understand the genetic diversity and population structure of alfalfa germplasm from the United States. In this study, the population structure and genetic diversity of six alfalfa cultivars of United States origin were investigated by microsatellite analysis with 40 individuals per cultivar. A total of 312 discernible alleles were amplified from the whole genome with an average of 31.2 alleles per locus. The average values of polymorphic information content and Shannon's information index w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…As our study is the first large study on S. rebaudiana genetic resources, there is no reference study. But, similar results have been observed in other outcrossing perennials such as alfalfa ( Medicago sativa ) [29], Dalmatian Pyrethrum ( Tanacetum cinerariifolium ) [30] or agronomic switchgrass ( Panicum virgatum ) [31]. The high level of genetic variability observed within populations of such species is most likely due to their partial or completely allogamous reproductive systems.…”
Section: Discussionsupporting
confidence: 73%
“…As our study is the first large study on S. rebaudiana genetic resources, there is no reference study. But, similar results have been observed in other outcrossing perennials such as alfalfa ( Medicago sativa ) [29], Dalmatian Pyrethrum ( Tanacetum cinerariifolium ) [30] or agronomic switchgrass ( Panicum virgatum ) [31]. The high level of genetic variability observed within populations of such species is most likely due to their partial or completely allogamous reproductive systems.…”
Section: Discussionsupporting
confidence: 73%
“…Using alfalfa germplasm (Medicago sativa L. subsp. sativa) (Yin et al, 2018) showed that genotype diversity was due to indiscriminate introduction of from various sources. Furthermore, pairing of the genotypes was associated more to individuals with possible common origin.…”
Section: Principal Component Biplotmentioning
confidence: 99%
“…Alfalfa (Medicago Sativa), a perennial cross-pollinated plant, is one of the most important forage crops in semi-arid and arid areas (Rong et al, 2017;Zhang et al, 2017) with greater commercial and ecological significance (Yin et al, 2018). However, cultivated alfalfa is a self-incompatible autotetraploid (2n = 4x = 32) plant with a very complex genome that hinders efforts to genetically improve the varieties (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%